The Role of Principal Leadership in Creating Effective Schools - Nurul Salis Alamin, Syarifah, Saepul Anwar, Nurul Azizah, Defi Firmansah (STAI Syaichona Moh. Cholil Bangkalan, 2025)
A principal is a skilled teacher tasked with leading a school, a place where students and teachers interact or where the teaching and learning process takes place. Principals are said to hold high standards for both staff and students. Individuals who establish routines for the school and are experienced in their responsibilities are called principals. Principals are expected to meet the nation's expectations as leaders. Therefore, it is crucial to have a principal with sufficient insight and the ability to direct the school organization. A principal acts as a manager, essentially planning, organizing, leading, and controlling. Managers who are capable of organizing, planning, controlling, and leading are essential for a company, where human resource careers can be nurtured and developed. This ensures that the organization can achieve its goals. The presence of a manager is crucial for achieving organizational goals and developing various types of knowledge.